Layered materials : electrochemical studies for sensing, energy applications and toxicity studies - Chia, Hui Ling (Nanyang Technological University, 2021)
As society has revolutionised, constant advancements in sensor and energy technologies are required. With the increasing complexity of samples and demand for more analysis to be made, it is of utmost importance to constantly improve the analytical capabilities of sensing platforms and develop sensors that are highly specific, have high sensitivity, are low in cost, easy to use, rapid and reliable. Furthermore, the current state-of-the-art electrocatalysts often involve precious metals, which are scarce, costly and suffer from poor stability, hampering their widespread application. Meanwhile, the ground-breaking discovery of graphene from graphite and the subsequent revelation of graphene’s extraordinary properties, has paved the way for the rediscovery of a plethora of layered materials. Layered materials possess a myriad of fascinating properties and hold great promise for a variety of applications. As such this thesis explored the electrochemistry of layered materials and exploited layered materials for the development of electrochemical sensing platforms and electrocatalysts. Herein, the dissertation investigated the viability of using MXenes and Group 14 graphane analogues for the development of highly sensitive second-generation electrochemical glucose biosensors. A highly sensitive glucose sensor with an ultralow limit of detection was also fabricated upon core-shell gold@silver nanorods decorated pnictogen nanosheets. Additionally, vanadium-doped molybdenum dichalcogenides were explored for the hydrogen evolution reaction, the oxygen evolution reaction and oxygen reduction reaction and the effects of varying the stoichiometry of vanadium dopants in bulk molybdenum dichalcogenides on their electrocatalytic activities were also investigated. Apart from studying the electrochemical properties and applications of layered materials, it is also perceived that there are growing concerns over the potential of these layered materials in causing new hazards and risks. As such, the thesis explored the cytotoxicity profiles of various emerging classes of layered materials, namely Group 5 transition metal ditellurides and pnictogen nanosheets. The findings in this dissertation represent a noteworthy first step towards enhancing our understanding of the electrochemical properties, applications and toxicological profiles of emerging classes of layered materials.